Determining hypoglycaemic and anti-adipogenic properties of phenolic-rich soya husk extract using in-vitro and in-vivo models - Tan, Seok Tyug (2012)
The growing incidence of obesity and diabetes seem to be an unavoidable trend in both developed and developing countries. Emerging evidence derived from epidemiological studies claim that sufficient intake of phenolics may effective in protecting human against the oxidative-stress related diseases such as cancers, cardiovascular diseases, diabetes, obesity and osteoporosis. Besides, numerous literatures reported that there is considerable concentration of health-promoting compounds in the outer layers of cereal grains and legumes, or specifically in the bran or hull (husk). However, the bran or hull from cereal grains and legumes are often considered as by-products in food processing industries, and is currently used only for animal feed or as fertilizer. Therefore, the present study aimed to explore the possibility and potentiality of soya husk in improving obesity-diabetes parameters. The present study begun with proximate composition determination and antioxidant analysis in grade A soya milk powder (GASP), grade B soya milk powder (GBSP) and soya husk powder (SHP). Findings from the present study showed that SHP had a significant higher fibre contents (74.41 ± 0.19%) of the powders tested, which in turn, also deposited its potentiality to appear as an interfering component for obesity-diabetes studies. Following, the three powders were subjected for antioxidant capacity analyses, free phenolics and isoflavones identification. Soya byproducts, for instance, GBSP and SHP in present study, have reported to contain significant amounts of bioactive compounds such as daidzein, gallic acid, vanilic acid, syringic acid, ferulic acid and chlorogenic acid. The hypoglycaemic of phenolic- rich soya husk powder extract (SHPE) were determined in-vitro with three different parameters whereas murine 3T3-L1 adipocytes were employed for evaluating the antiadipogenic properties of SHPE. Collectively, the hypoglycaemic properties of SHPE were successfully demonstrated in three parameters studied. In addition, SHPE with lower concentrations (25-100 μg/ml) were also regarded as potential anti-adipogenic agent due to their ability in reducing lipid droplet accumulation (48.48 ± 0.03 to 102.02 ± 2.00%), triglyceride accumulation (5.68 ± 0.07 to 11.17 ± 0.14 mg/dl), GPDH activity (49.13 ± 0.15 to 91.44 ± 0.04%) and subsequently down-regulating PPARγ expression in 3T3-L1 adipocytes. Since in-vitro model has provided promising findings, evaluation on the hypoglycaemic and anti-adipogenic properties of SHPE was further expanded using an in-vivo model. It is showed that short-term of SHPE supplementations (250 mg/kg BW or 500 mg/kg BW) improved the biomarker parameters (fasting plasma blood glucose, insulin level and lipid profiles) of obese-diabetic rats. Additionally, the supplementations were also shown to slightly up-regulated PPARγ expression (4.81 ± 1.31 to 6.69 ± 2.71%) in adipocytes of experimental rats. Therefore, SHPE could be considered as potential hypoglycaemic and anti-adipogenic agents. In line with the reported promising effects, the present study has revealed the possibility of soya husk to be used for the development of hypoglycaemic and anti-adipogenic nutraceuticals.